The Hypothetical Inclusion Membrane Protein CPSIT_0846 Regulates Mitochondrial-Mediated Host Cell Apoptosis via the ERK/JNK Signaling Pathway - Tang, Ting; Wu, Haiying; Chen, Xi; Chen, Li; Liu, Luyao; Li, Zhongyu; Bai, Qinqin; Chen, Yuyu; Chen, Lili (Frontiers in Cellular and Infection Microbiology, 2021)
Chlamydia psittaci is an important zoonotic factor associated with human and animal atypical pneumonia. Resisting host cell apoptosis is central to sustaining Chlamydia infection in vivo. Chlamydia can secrete inclusion membrane proteins (Incs) that play important roles in their development cycle and pathogenesis. CPSIT_0846 is an Inc protein in C. psittaci identified by our team in previous work. In the current study we investigated the regulatory role of CPSIT_0846 in HeLa cell apoptosis, and explored potential mechanisms. The results showed that HeLa cells treated with CPSIT_0846 contained fewer apoptotic bodies and exhibited a lower apoptotic rate than untreated cells either with Hoechst 33258 fluorescence staining or flow cytometry with or without induction by staurosporine (STS). CPSIT_0846 could increase the phosphorylation of the extracellular signal-regulated kinases 1/2 (ERK1/2) or stress-activated protein kinases/c-Jun amino-terminal kinases (SAPK/JNK) signaling pathways, and the Bcl-2 associated X protein (Bax)/B cell lymphoma 2 (Bcl-2) ratio, levels of cleaved caspase-3/9 and cleaved Poly-ADP-ribose polymerase (PARP) were significantly up-regulated following inhibition of ERK1/2 or SAPK/JNK pathways with U0126 or SP600125. After carbonyl cyanide 3-chlorophenylhydrazone (CCCP) treatment, the mitochondrial membrane potential (MMP) of cells was significantly decreased in control group, but stable in the CPSIT_0846 treated one, and less cytochrome c (Cyt.c) was released into the cytoplasm. Inhibition of the ERK1/2 or SAPK/JNK pathway significantly decreased the JC-1 red-green fluorescence signal, and promoted Cyt.c discharge into the cytoplasm in HeLa cells treated with CPSIT_0846. In conclusion, CPSIT_0846 can regulate mitochondrial pathway-mediated apoptosis in HeLa cells by activating the ERK/JNK signaling pathway.